Adolescents' evaluations of those who challenge exclusive and inclusive peer norms. (4th July 2022) - Hitti, Aline; Killen, Melanie
Abstract: Early and middle adolescents' judgements and reasonings about peers who challenge exclusive and inclusive peer group norms were examined across three studies with varying intergroup contexts. Study 1 participants included ( N = 199) non‐Arab American participants responding to an Arab American/non‐Arab American intergroup context. Study 2 included ( N = 123) non‐Asian and ( N = 105) Asian American participants responding to an Asian/non‐Asian American intergroup context. Study 3 included ( N = 275) Lebanese participants responding to an American/Lebanese intergroup context. Across all three studies participants responded to ingroup and outgroup deviant group members who challenged their peer groups to either include or exclude an outgroup peer with similar interests. Findings indicated that adolescents approved of peers who challenged exclusive peer norms and advocated for inclusion of an ethnic and cultural outgroup, and disapproved of peers who challenged inclusive group norms and advocated for exclusion. Non‐Arab and non‐Asian American adolescents displayed ingroup bias when evaluating a deviant advocating for exclusion. Additionally, age differences were found among Asian American adolescents. Findings will be discussed in the light of intergroup research on those who challenge injustices.